2022
DOI: 10.1002/ps.7060
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sublethal effects of insecticides used in the management of Plutella xylostella (Lepidoptera: Plutellidae) on the predator Cycloneda sanguinea L. (Coleoptera: Coccinellidae)

Abstract: BACKGROUND The application of synthetic insecticides is the main strategy used to reduce the damage caused by the diamondback moth Plutella xylostella in commercial Brassica crops. However, incorrect insecticide use can cause biological and ecological disturbances in agroecosystems. Cycloneda sanguinea is a generalist voracious predator and is distributed widely in cultivated and noncultivated ecosystems. This study investigated the efficiency of four insecticides for the control of P. xylostella and the letha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In contrast, the sublethal concentrations of cyantraniliprole and beta-cypermethrin did not show any significant effect on the life history of Helicoverpa assulta [48] and P. xylostella [49], respectively. Besides, da Silva et al [50] reported that chlorantraniliprole (<10% mortality) and methomyl (0% mortality) registered very negligible toxicity to P. xylostella at their sublethal levels. This phenomenon might be attributable to the typical symptoms of positive fitness effects of sublethal insecticides exposure to insect pests [51].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…In contrast, the sublethal concentrations of cyantraniliprole and beta-cypermethrin did not show any significant effect on the life history of Helicoverpa assulta [48] and P. xylostella [49], respectively. Besides, da Silva et al [50] reported that chlorantraniliprole (<10% mortality) and methomyl (0% mortality) registered very negligible toxicity to P. xylostella at their sublethal levels. This phenomenon might be attributable to the typical symptoms of positive fitness effects of sublethal insecticides exposure to insect pests [51].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Sublethal concentrations of insecticides can affect many physiological parameters such as development, longevity, and fecundity (Zhou et al 2017;Lu et al 2020;Wu et al 2022), as well as mobility (da Silva et al 2022), and feeding behaviour (Koo et al 2015;Zeng et al 2016). These effects can vary according to the species and the insecticides used.…”
Section: Introductionmentioning
confidence: 99%